SCREENING IVA TEST PADA PEGAWAI UNIVERSITAS CENDERAWASIH - Hasmi, Hasmi; Tingginehe, Rosmin Mariati; Rantetoding, Septevanus (LPPM Uncen, 2023)
More than half a million women contracted cervical cancer, and as a result, about 342,000 women died. WHO's global strategy for cervical cancer elimination, endorsed by the World Health Assembly in 2020, calls for 70% of women worldwide to have regular cervical disease screening for early treatment and avoid death. The purpose of this service is the IVA Test Screening for Cenderawasih University Employees to determine mothers who experience servitis, white spots, and early invasive stage. The screening was carried out on 7 -9 September 2022 at the Mobile Clinic located in the yard of the FKM Uncen Building by the Papua Provincial Health Office Team together with the FKM Uncen service team. The results found that there were 2 (3.6%) whose IVA test results were positive and 53 (96.4%) whose IVA test results were negative. There were 11 (20%) who had cervical inflammation (cervicitis). There were 17 (30.9%) who had vaginal discharge. There were 2 (3.6%) who had cervical lesions precancerous Keywords: Screening; IVA test; cervical cancer